Model Quantum Learning Pendidikan Agama Islam - ‘Ulyan, Mohammad (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
Quantum learning is an active learning model, strategy, and approach that seeks toturn the interaction between teachers, students, and their environment into light.The light here is intended as a radiance as a result of positive interactions in learning.Therefore, in implementing this learning model, it is expected that there is anorchestration between context and content. It is certainly packed in a passionate, funand easy learning frame for students. With the principle of